2011
DOI: 10.1080/02602930903432074
|View full text |Cite
|
Sign up to set email alerts
|

An in‐depth study on the impact of external quality assurance

Abstract: After more than two decades of external quality assurance, there is an increasing interest in questions concerning the impact and effects of this activity. Following an external evaluation of NOKUT -the Norwegian quality assurance agency, this article studies the impact of external quality assurance in detail by analysing quantitative and qualitative feedback from those exposed to evaluations conducted by this agency. The study provides information on the impact of various methods used, how impact is perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 20 publications
2
86
0
4
Order By: Relevance
“…The most recent study using quantitative data undertaken by Stensaker et al (2010) in Norway suggests that national quality monitoring by the external agency had positive impact with 77% suggesting high and moderate positive impact. Their study suggests that the areas of significant positive impact as a result of external monitoring include: effects on new routines and procedures (45.7%); effects on the scholarly discussion on learning and teaching (43.5%); effects on the quality of learning and teaching (39.1%); and effects on staff engagement in learning and teaching questions (34.8%).…”
Section: Shahmentioning
confidence: 94%
“…The most recent study using quantitative data undertaken by Stensaker et al (2010) in Norway suggests that national quality monitoring by the external agency had positive impact with 77% suggesting high and moderate positive impact. Their study suggests that the areas of significant positive impact as a result of external monitoring include: effects on new routines and procedures (45.7%); effects on the scholarly discussion on learning and teaching (43.5%); effects on the quality of learning and teaching (39.1%); and effects on staff engagement in learning and teaching questions (34.8%).…”
Section: Shahmentioning
confidence: 94%
“…These issues also relate to the question of effectiveness of accreditation and its impact on institutional structures (Stensaker et al 2011;Cardoso, Rosa, and Stensaker, 2015). Our research has shown that the accreditation procedure is unable to capture the full dynamics of the process that underpins learning in an undergraduate programme and in relation to the involvement of the professional field.…”
Section: Discussionmentioning
confidence: 95%
“…Within this context, the accreditation process usually addresses the views of the government and, to a certain extent, academia (Stensaker et al 2011;Serap and Cress 2014), in terms of whether the institution qualifies for a certain status (Välimaa 2004). Employers and students are rarely mentioned, despite their obvious role in the accountability and transparency of the process (Santiago et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Through the assessment of an EQA body, an institution or program can be evaluated to determine whether its operation meets certain accreditation standards to ensure educational quality and accountability (Kells 1995;Rosa and Amaral 2007). In contrast to accreditation, self-accreditation enables individual institutions to determine how their performance is in accord with the institutional missions (Stensaker et al 2011). Self-accreditation demonstrates a stronger improvement-oriented purpose.…”
Section: Purpose: Accountability Versus Improvementmentioning
confidence: 99%